Analytical Study of Politics in Bangladesh : Ages of Sheikh Hasina and Khaleda Zia’s Dictates - Mohammad Eisa Ruhullah; Zuly Qodir (International Journal of Islamic Khazanah, 2021)
Establishing a healthy and competitive democratic method remained a distant dream for a lengthy time to get to Bangladesh. The attain sociopolitical integration and sustainable development which is essential for establishing a peaceful democratic society in Bangladesh. This research to examine the leadership of H. E. Shaikh Hasina and Begum Khaleda Zia with Bangladesh Awami League and Bangladesh National Party. By using a qualitative approach this research aims The study to measure the implication of democracy via both leaders during their regimes. It must find out the solution of the current problems of the political transformation and accountability among the political parties (administrations). The writing obtains to a final decision on the leading method of both ladies in Bangladesh was lacking sustainable development in politics and lacking mutual trust plus understanding among them. Moreover, this study explores that the real challenge to a free and fair national election in Bangladesh is not constitutional or administrative but political. Political parties themselves create electoral problems in Bangladesh. Thus, to defeat the political crisis by political institutionalization among responsibility and tolerance is vital for the country to exercise democracy. In short, the future researchers might straighten in their further study on the governmental investigation in Bangladesh